Perlindungan Hukum Bagi Pekerja Rumah Tangga Sebagai Korban Tindak Kekerasan - Yasser Arafat (Diktum: Jurnal Ilmu Hukum, 2022)
Unbalanced work relations between domestic workers and employers make domestic workers vulnerable to being victims of violence. The existence of Law Number 13 of 2003 concerning Manpower is expected to be the legal umbrella for the protection of workers, including domestic workers. The purpose of this study is to examine the position of domestic workers in Law Number 13 of 2003 concerning Manpower and legal protection for acts of violence committed against domestic workers. The research method uses normative legal research by examining primary and secondary legal sources and analyzing the use of the syllogism method and interpretation method using deductive thinking patterns. The results of this study indicate that the position of domestic workers in Law Number 13 of 2003 concerning Manpower is very weak because the law does not adequately provide protection to domestic workers if one day there is a dispute between domestic workers, one of which is in the form of disputes due to acts of violence. violence against domestic workers. This is because domestic workers are not included in the labor protected by the law. As for the protection of domestic workers from acts of violence has been provided by the Criminal Code and Law Number 23 of 2004 concerning the Elimination of Domestic Violence.